Taiwan yearbook 2006. (Taiwan : Government Information Office, 2006)
Sumario: Este disco compacto presenta información general de Taiwan relacionados con su historia, geografía, idioma, gobierno, economía, entre otros.
Requerimientos del sistema: Windows 95/98/ME 2000/XP; Best viewe with IE 5.x; Netscape Comunicator 7.x or Forefox 2.0 or higher at 800x600 resolution
Keywords: TAIWAN -- ANUARIOS; TAIWAN -- CIVILIZACION; TAIWAN -- HISTORIA; TAIWAN -- VIDA SOCIAL Y COSTUMBRES; TAIWAN